Waspadai Bahaya Kriminalisasi pada Anak Usia Dini - Hafizah Tulaini (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
Abstract, The criminalization of early childhood in the family environment has become a worrying issue in the modern era. This phenomenon occurs when young children experience negative treatment or stigma which can lead to labeling or exclusion in the home environment, whether consciously or not. Various actions that are considered "deviant" by parents or family, such as behavior that is considered naughty or disobedient, are often treated harshly or even accompanied by threats of excessive punishment that should not be applied at that age. This behavior can trigger long-term effects on children's psychological and emotional development and has the potential to influence the formation of their identity and behavior in the future. This article will discuss the dangers of criminalization in early childhood, the factors that cause it and efforts to prevent it.